CLK2 Condensates Reorganize Nuclear Speckles and Induce Intron Retention - Bing Wang; Jing Li; Yanyang Song; Xuhui Qin; Xia Lu; Wei Huang; Chentai Peng; Jinxia Wei; Donghui Huang; Wei Wang (Advanced Science)
Abstract Intron retention (IR) constitutes a less explored form of alternative splicing, wherein introns are retained within mature mRNA transcripts. This investigation demonstrates that the cell division cycle (CDC)‐like kinase 2 (CLK2) undergoes liquid–liquid phase separation (LLPS) within nuclear speckles in response to heat shock (HS). The formation of CLK2 condensates depends on the intrinsically disordered region (IDR) located within the N‐terminal amino acids 1‐148. Phosphorylation at residue T343 sustains CLK2 kinase activity and promotes overall autophosphorylation, which inhibits the LLPS activity of the IDR. These CLK2 condensates initiate the reorganization of nuclear speckles, transforming them into larger, rounded structures. Moreover, these condensates facilitate the recruitment of splicing factors into these compartments, restricting their access to mRNA for intron splicing and promoting the IR. The retained introns lead to the sequestration of transcripts within the nucleus. These findings extend to the realm of glioma stem cells (GSCs), where a physiological state mirroring HS stress inhibits T343 autophosphorylation, thereby inducing the formation of CLK2 condensates and subsequent IR. Notably, expressing the CLK2 condensates hampers the maintenance of GSCs. In conclusion, this research unveils a mechanism by which IR is propelled by CLK2 condensates, shedding light on its role in coping with cellular stress.